1993
DOI: 10.1016/0735-1097(93)90232-p
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and sympathetic activity in patients with congestive heart failure

Abstract: Neither the infusion of angiotensin II nor the acute administration of enalaprilat significantly alters the activity of the sympathetic nervous system as reflected by plasma norepinephrine or systemic venous norepinephrine spillover in patients with chronic congestive heart failure. These data weaken the hypothesis that angiotensin II is an important regulator of sympathetic activity in congestive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…A more confusing picture emerges in whole-animal experiments designed to isolate the contributions of the peripheral sympathetic nervous system: AII infusion can facilitate, 4 suppress, 5 or have no effect 6 on norepinephrine release from postganglionic sympathetic neurons. In humans, a similar pattern of sympathetic neural responses has been reported, with some studies showing increased norepinephrine spillover 3 and others showing no response 7 or decreased norepinephrine release 3,7,8 in response to AII. In other excitable cell types such as cardiomyocytes or vascular smooth muscle cells, a paradoxical response has also been reported.…”
mentioning
confidence: 75%
“…A more confusing picture emerges in whole-animal experiments designed to isolate the contributions of the peripheral sympathetic nervous system: AII infusion can facilitate, 4 suppress, 5 or have no effect 6 on norepinephrine release from postganglionic sympathetic neurons. In humans, a similar pattern of sympathetic neural responses has been reported, with some studies showing increased norepinephrine spillover 3 and others showing no response 7 or decreased norepinephrine release 3,7,8 in response to AII. In other excitable cell types such as cardiomyocytes or vascular smooth muscle cells, a paradoxical response has also been reported.…”
mentioning
confidence: 75%
“…Concerning relevance to heart failure, there are no studies in which angiotensin II has been introduced directly into the human central nervous system, but elegant work mainly by Zucker et al [20] has shown a role for central angiotensin II, acting through stimulation of nitric oxide, in the activation of the SNS in animal models of heart failure [20,22,23]. Presynaptic facilitation of norepinephrine release has been demonstrated in the normal human forearm circulation at very high concentrations of angiotensin II [24] but not in normal humans undergoing mild to moderate degrees of sympathostimulation during decreased central venous volume, nor has it been demonstrated in patients with heart failure with high baseline sympathetic tone [25][26][27][28]. However, a physiologic role for angiotensin II as an inhibitor of normal baroreflexmediated reduction in heart rate and sympathetic activity has been demonstrated in normal humans and animals [29,30].…”
Section: Effects Of the Raas On The Sympathetic Nervous Systemmentioning
confidence: 96%
“…The data come from studies that have examined the chronic effects of ACEI on sympathoactivation in heart failure. Acutely, administering ACEI therapy to a patient with heart failure does not have much, if any, effect on plasma norepinephrine or norepinephrine release [26]. However, after several months of therapy with ACEI, a reduction in muscle sympathetic nerve activity can be demonstrated, and in turn linked to an improvement in baroreflex function [32•].…”
Section: Effects Of the Raas On The Sympathetic Nervous Systemmentioning
confidence: 99%
“…There is also evidence, albeit conflicting, that the sympathetic nervous system is activated by the renin-angiotensin system. [1][2][3][4][5][6][7][8][9][10][11][12][13] This activation supposedly occurs through stimulation of angiotensin II receptors within the central nervous system and/or stimulation of presynaptic angiotensin II receptors located at sympathetic nerve terminals. When investigating the sympathetic nervous system and its interaction with the renin-angiotensin system, the heart is of particular interest.…”
mentioning
confidence: 99%